Using sparse control methods to identify sources in linear diffusion-convection equations. (3rd October 2019) - Casas, E; Kunisch, K
Abstract: Techniques from sparse control theory are proposed to approximate initial conditions for diffusion-convection equations. Existence and uniqueness of optimal controls are proven, and necessary and sufficient optimality conditions are derived. From these conditions the sparsity structure of the solutions is derived, which relates to identification of the sources to be reconstructed.